Nigerian Art Music - Bode Omojola (IFRA-Nigeria, 2021)
ART MUSIC IN NIGERIA is the most comprehensive book on the works of modem Nigerian composers who have been influenced by European classical music. Relying on over 500 scores, archival materials and interviews with many Nigerian composers, the author traces the historical developments of this new idiom in Nigeria and provides a critical and detailed analysis of certain works. Written in a refreshing and lucid style and amply illustrated with music examples, the book represents a milestone in m...